1996
DOI: 10.1044/jshr.3902.311
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Correlates of Breathy Vocal Quality: Dysphonic Voices and Continuous Speech

Abstract: In an earlier study, we evaluated the effectiveness of several acoustic measures in predicting breathiness ratings for sustained vowels spoken by nonpathological talkers who were asked to produce nonbreathy, moderately breathy, and very breathy phonation (Hillenbrand, Cleveland, & Erickson, 1994). The purpose of the present study was to extend these results to speakers with laryngeal pathologies and to conduct tests using connected speech in addition to sustained vowels. Breathiness ratings were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
372
2
27

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(412 citation statements)
references
References 19 publications
11
372
2
27
Order By: Relevance
“…1 Inharmonic (noise) energy also contributes significant excitation (e.g., Hillenbrand & Houde, 1996), particularly in female voices in which persistent glottal gaps may be present (e.g., Holmberg, Hillman, Perkell, Guiod, & Goldman, 1995;Linville & Fisher, 1992), in male or female "sexy" voice (Henton & Bladon, 1985), and in pathologic phonation. For example, Holmberg et al found that for women with normal voice, most vowel productions displayed a mix of harmonic energy and noise in the F3 region; some showed mostly noise, and only a few tokens were produced with predominantly harmonic energy.…”
Section: Existing Measures Of Source Spectral Slopementioning
confidence: 99%
“…1 Inharmonic (noise) energy also contributes significant excitation (e.g., Hillenbrand & Houde, 1996), particularly in female voices in which persistent glottal gaps may be present (e.g., Holmberg, Hillman, Perkell, Guiod, & Goldman, 1995;Linville & Fisher, 1992), in male or female "sexy" voice (Henton & Bladon, 1985), and in pathologic phonation. For example, Holmberg et al found that for women with normal voice, most vowel productions displayed a mix of harmonic energy and noise in the F3 region; some showed mostly noise, and only a few tokens were produced with predominantly harmonic energy.…”
Section: Existing Measures Of Source Spectral Slopementioning
confidence: 99%
“…This is in accordance with the assumption that a poor glottal closure leads to a stronger attenuation of the harmonics [3,10]. On the other hand, the mean of the aphonic group (-8.4dB) can be interpreted as indication of the spectral shape of the noise excitation.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, the mean of the aphonic group (-8.4dB) can be interpreted as indication of the spectral shape of the noise excitation. This noise can be described as bandpass-filtered white noise [10], so that the negative value reflects the attenuation of low-frequent spectral energy. However, the transition from highly disturbed voices that still exhibit a harmonic structure (e.g., aep) to complete aphonia remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rainbow Passage has been used in a variety of acoustic and perceptual studies of speech, including investigations of talker differences (e.g., Gelfer and Schofield, 2000) and the speech of clinical populations (e.g., Baker et al, 1997;Hillenbrand and Houde, 1996;McHenry, 1999;Sapienza et al, 1999).…”
Section: Stimulus Materialsmentioning
confidence: 99%